Understanding revenge pornography: public perceptions of revenge pornography and victim blaming - Bothamley, Sarah; Tully, Ruth (Emerald, 2017)
Purpose: The disclosure of private images with the intent of causing distress is often described as ‘revenge pornography’. In the UK, this newly legislated crime has received a high level of media attention following several high profile cases, however there is a paucity of research in this area. Methods: 168 adults (UK general public) completed an online survey using a vignette approach. Views of the influence of perpetrator-victim relationship length and reason for termination were considered alongside perception of an offence, the necessity of police intervention, what extent revenge pornography creates psychological harm in victims, and victim blaming. Findings: Perpetrator-victim relationship length and reason for relationship breakdown did not influence perceptions of victim blame. Participants believed that the situation described in the vignettes was likely to be an offence, and that police intervention is somewhat necessary. Participants believed that the scenario was ‘very likely’ to create fear, and ‘moderately likely’ to create psychological/mental harm in victims. In line with the literature relating to stalking and sexual assault, men blamed the victim significantly more than women. Furthermore, women rated police intervention significantly more necessary than men. Implications: The public are recognising that revenge pornography is an offence, with consequences being fear and psychological harm, showing an awareness of the impact on victims. However, there are sex differences in the perceptions of revenge pornography and victim blame and this could be addressed by raising awareness of this crime. This research, which highlights that the public are aware of some of the harm caused, may encourage victims in coming forward to report such a crime. Originality: There is a paucity of research into revenge pornography, and this study is one of the first in this area.